Characterization of three ciliopathy pedigrees expands the phenotype associated with biallelic C2CD3 variants. (December 2018) - Boczek, Nicole; Hopp, Katharina; Benoit, Lacey; Kraft, Daniel; Cousin, Margot; Blackburn, Patrick; Madsen, Charles; Oliver, Gavin; Nair, Asha; Na, Jie; Bianchi, Diana; Beek, Geoffrey; et al.
Abstract Whole exome sequencing (WES) is utilized in diagnostic odyssey cases to identify the underlying genetic cause associated with complex phenotypes. Recent publications suggest that WES reveals the genetic cause in ~25% of these cases and is most successful when applied to children with neurological disease. The residual 75% of cases remain genetically elusive until more information becomes available in the literature or functional studies are pursued. WES performed on three families with presumed ciliopathy diagnoses, including orofaciodigital (OFD) syndrome, fetal encephalocele, or Joubert-related disorder, identified compound heterozygous variants inC2CD3 . Biallelic variants inC2CD3 have previously been associated with ciliopathies, including OFD syndrome type 14 (OFD14; MIM: 615948). As three of the six identified variants were predicted to affect splicing, exon-skipping analysis using either RNA sequencing or PCR-based methods were completed to determine the pathogenicity of these variants, and showed that each of the splicing variants led to a frameshifted protein product. Using these studies in combination with the 2015 ACMG guidelines, each of the six identified variants were classified as either pathogenic or likely pathogenic, and are therefore likely responsible for our patients' phenotypes. Each of the families had a distinct clinical phenotype and severity of disease, extending from lethal to viable. These findings highlight that there is a broad phenotypic spectrum associated withC2CD3 -mediated disease and not all patients present with the typical features of OFD14.